A IMPUGNAÇÃO DAS DECISÕES INTERLOCUTÓRIAS EM CONTRARRAZÕES AO RECURSO ORDINÁRIO NO PROCESSO DO TRABALHO: UM ESTUDO A PARTIR DO § 1º DO ART. 1.009 DO CPC/2015 - Martinelli, Andre Silva (2020)
It studies the dialogue between CPC/2015 rules and the labor proceedings. It investigates the Paragraph 1 of the art. 1.009, of CPC/2015, and the possibility to cross-appeal. Next, it demonstrates the impact of changing the system of interlocutory decisio